An Analysis of Toefl Takers Anxiety and Their Toefl Score on 8th Semester of English Education UINFAS Bengkulu - Chista Riyanda Putri; Fera Zasrianita; Ferry Susanto; Ari Andre Rianyansa (Jurnal Pendidikan dan Profesi Keguruan, 2025)
​​This study investigates the factors contributing to TOEFL test anxiety and its relationship with test performance among eighth-semester English Education students at UIN Fatmawati Sukarno Bengkulu. Despite the growing importance of English proficiency in Indonesia, little attention has been paid to the psychological aspects influencing students’ TOEFL outcomes. Employing a mixed-method descriptive design, this study involved 20 students who had recently taken the TOEFL test. Data were collected through an adapted Test Anxiety Inventory quest​ionnaire and semi-structured interviews and analyzed using descriptive statistics and thematic analysis. The results revealed that fear and cardiovascular symptoms were the most dominant indicators of anxiety, whereas sensory symptoms showed the lowest mean score. High anxiety levels, particularly those related to fear and sleep disturbance, were found to negatively affect TOE​FL scores. The findings suggest that TOEFL anxiety encompasses both psychological (fear and tension) and physiological (cardiovascular and respiratory) dimensions that jointly influence performance. Institutions should provide pre-test workshops, relaxation training, and time-management coaching to help students manage anxiety and improve test readiness.